Tingkat depresi pada lansia yang tinggal di komunitas ditinjau dari karakteristik lansia - Ismy Salsabila Yuliani; Sugiharto Sugiharto (Holistik Jurnal Kesehatan, 2022)
Background: The elderly will experience changes either physically, mentally, or socially. These changes can decrease daily productivity. The degenerative process that occurs can make the elderly vulnerable to various diseases. Decreased productivity, illness or perceived complaints, loss of life partner and children, limited social activities, and feelings of sadness and worthlessness can result in depression in the elderly.Purpose: To analyze the level of depression of the elderly indwelling community based on their characteristics.Method: This descriptive study used a cross-sectional approach, the total sampling technique used was obtained 151 respondents who met the criteria, among others; elderly aged >60 years, willing to be respondents, and elderly registered as residents of Bugangan Village, Kedungwuni District, Pekalongan Regency.The results of the Mini-Mental State Examination (MMSE) 25–30 are classified into the normal category and to know the level of depression using instrument the Geriatric Depression ScaleResults: The results showed that of the elderly who lived in the indwelling community the average age is 69 years (SD = 5.53), 57.6% are female, 65.6% of respondents are in elementary school, and 83 respondents are still actively working with income below the minimum wage. Most of the respondents work as farm laborers, convection workers, and traders. The majority of respondents (90.7%) live with their families. A total of 126 respondents are still active in social activities. As well as a number of 78 respondents with widower/widow status. Almost one-third (72.8%) were normal without depression.Conclusion: The presence of family and the existence of social activities can reduce the risk of depression among elderly indwelling-community. Social support, especially from their family, is the most important and needed among elderly.Keywords: Depression; Elderly; Indwelling-CommunityPendahuluan: Lansia akan mengalami perubahan baik fisik, mental, dan sosial. Kondisi ini dapat berakibat terjadinya penurunan produktivitas sehari-harinya. Proses degeneratif yang terjadi dapat menjadikan lansia rentan terhadap berbagai penyakit. Produktivitas yang menurun, adanya penyakit atau keluhan yang dirasakan, kehilangan pasangan hidup dan anak-anak, adanya keterbatasan aktivitas sosial, dan rasa sedih dan tidak berguna dapat berakibat terjadinya depresi pada lansia.Tujuan: Penelitian ini bertujuan untuk mengetahui tingkat depresi pada lansia yang tinggal di komunitas ditinjau dari karakteristik lansia.Metode: Penelitian deskriptif menggunakan teknik total sampling didapatkan 151 responden yang memenuhi kriteria antara lain;  lansia berumur >60 tahun, bersedia menjadi responden, dan lansia yang terdaftar sebagai penduduk Desa Bugangan Kecamatan Kedungwuni Kabupaten Pekalongan.Hasil penilaian Mini Mental State Examination (MMSE)  25–30 tergolong ke dalam kategori normal dan  untuk melihat tingkat depresi dipakai instrumen Geriatric Depression Scale.Hasil: Hasil penelitian menunjukkan bahwa lansia yang tinggal di komunitas rata-rata usia 69 tahun (SD =5.53), 57.6% berjenis kelamin perempuan, 65.6% responden tidak sekolah, 83 responden masih aktif bekerja dengan pendapatan dibawah UMR. Kebanyakan responden bekerja sebagai buruh tani, buruh konveksi, dan pedagang. Mayoritas responden (90.7%) tinggal dengan keluarga. Sebanyak 126 responden masih aktif dengan kegiatan sosial. Serta sejumlah 78 responden berstatus Duda/Janda. Kebanyakan responden berada dalam kondisi normal tanpa mengalami depresi (72.8%).Simpulan: Keberadaan lansia tinggal di komunitas yang masih memungkinkan berkumpul dengan keluarga dan beraktivitas sosial kemasyarakatan dapat menekan risiko terjadinya depresi. Dukungan sosial, terutama dari keluarga merupakan hal yang penting dan sangat dibutuhkan bagi para lansia.